An Overview Of The Immediate Execution Of Amar Decisions (Uitvoebaar Bij Voorad ) In Civil Cases in The Kabanjahe State Court - Aries Shandy Pasca Ginting (Institute Of computer Science (IOCS), 2020)
The decision immediately (uitvoerbaar bij voorraad) is a breakthrough against the slow judicial process. Through the uitvoerbaar bij voorraad institution, the Court's decision can be executed even though the decision has not yet obtained permanent legal force. However, this uitvoerbaar bij voorraad turned out to cause many problems in its implementation practice. One of the problems that often occurs is the process of executing decisions immediately. The District Court as the spearhead of executing the decision immediately (uitvoerbaar bij voorraad) often encounters obstacles in executing the decision. Normative research is conducted by examining laws and regulations, legal materials, and other materials related to the writing of this thesis. Sociological research was conducted by conducting research at the Kabanjahe District Court. The types of data used are primary data and secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials.The existence of a guarantee by the applicant for execution is one of the conditions for the immediate execution of the decision. Without this guarantee, the execution of the decision cannot be carried out immediately. Barriers to the immediate execution of the decision (uitvoerbaar bij voorraad) at the Kabanjahe District Court were not the immediate issuance of an execution permit by the Head of the Medan High Court, the applicant for execution was unable to submit guarantees, and obstacles in the field in the form of mass mobilization by the Respondent for execution. If the execution of the decision is immediately delayed (uitvoerbaar bij voorraad), the District Court of Kabanjahe takes measures to overcome the delay in execution. In the event that the execution of the decision is immediately hampered because the chairman of the Medan High Court has not issued an execution permit immediately, then the only way to implement the contents of the decision is to wait until the decision has permanent legal force. If the execution delay is due to the inability of the execution applicant to provide guarantees, then the Chief of the Kabanjahe District Court will advise the execution applicant to borrow money from family or relatives, friends, or the bank. In the event that the execution is delayed due to obstacles in the field, the Court bailiff and the police will take persuasive efforts. the Head of the Kabanjahe District Court will advise the execution applicant to borrow money from family or relatives, friends, or the bank. In the event that the execution is delayed due to obstacles in the field, the Court bailiff and the police will take persuasive efforts. the Head of the Kabanjahe District Court will advise the execution applicant to borrow money from family or relatives, friends, or the bank. In the event that the execution is delayed due to obstacles in the field, the Court bailiff and the police will take persuasive efforts.